Analysis of the State Ownership Realization Process on the Example of Kazakhstan - CHEREYEVA, Bakhytgul Tulegenovna; MALYARENKO, Olga Ivanovna; ABAYEVA, Gulder Ivanovna; MAYER, Olga Iosifovna; OSTRYANINA, Tatyana Kenzhebekovna (Journal of Advanced Research in Law and Economics, 2019)
The research sets out the theoretical and methodological foundations of state property management. The use of privatization as the main tool for managing the public sector of the economy is shown, as a proof of which, a review of studies on reforming the economies of various countries is carried out, the main methodology and the results are shown. The authors chose a dynamically developing country of the post-socialist space as an object of research, where an unsuccessful attempt to reform the public sector has already been made, and today, the second one is being conducted. The study uses statistical data from 1991-2004 and 2014-2018, in the context of two periods of privatization of Kazakhstan. The authors give preliminary results of the current reform of the privatization of property and give alternative ways to reduce the public sector of the economy. It is concluded that the problem of quantitative and qualitative growth of the public sector can be solved not only through privatization, but also by maintaining restrictions and requirements on state-owned companies. In the end, this will lead to the promotion of healthy competition; improving the investment climate; increasing business activity and labor productivity, which is so necessary for countries with developing economies.